Specificity and sensitivity of the SeLECT score in predicting late seizures in patients undergoing intravenous thrombolytic treatment and the effect of diabetes mellitus and leukoaraiosis - Dinç, Yasemin; Demir, Aylin Bican; Özkaya, Güven; Bakar, Mustafa (Arquivos de Neuro-Psiquiatria, 2023)
Background Seizures after stroke can negatively affect the prognosis of ischemic stroke and cause a decrease in quality of life. The efficacy of intravenous (IV) recombinant tissue plasminogen activator (rt-PA) treatment in acute ischemic stroke has been demonstrated in many studies, and IV rt-PA treatment has been increasingly used around the world. The SeLECT score is a useful score for the prediction of late seizures after stroke and includes the severity of stroke (Se), large artery atherosclerosis (L), early seizure (E), cortical involvement (C), and the territory of the middle cerebral artery (T). However, the specificity and sensitivity of the SeLECT score have not been studied in acute ischemic stroke patients that received IV rt-PA treatment.Objective In the present study, we aimed to validate and develop the SeLECT score in acute ischemic stroke patients receiving IV rt-PA treatment.Methods The present study included 157 patients who received IV thrombolytic treatment in our third-stage hospital. The 1-year seizure rates of the patients were detected. SeLECT scores were calculated.Results In our study, we found that the SeLECT score had low sensitivity but high specificity for predicting the likelihood of late seizure after stroke in patients administered IV rt-PA therapy. In addition to the SeLECT score, we found that the specificity and sensitivity were higher when we evaluated diabetes mellitus (DM) and leukoaraiosis.Conclusion We found that DM was an independent risk factor for late seizures after stroke in a patient group receiving thrombolytic therapy, and late seizures after stroke were less frequent in patients with leukoaraiosis.
Keywords: Stroke; Seizures; Intravenous Administration; Tissue Plasminogen Activator